Efeitos do lockdown sobre as internações eletivas no Brasil durante a pandemia de COVID-19 - Lopes, Maria Lêticia (2022)
Between 2020 and 2021, the COVID-19 pandemic advanced in the number of cases and deaths. Most countries, including Brazil, have enacted measures to contain the spread of this disease, such as strict social isolation policies (Lockdown). Several interventions were adopted in the health services management, causing the damming of visits and hospitalizations for diseases not related to COVID-19, especially those of an elective nature. In this context, the objective of this work is to estimate the impact of the lockdown measure on elective weekly hospitalizations not related to COVID-19, using data on hospitalizations, deaths, and bed supply, as well as the dates of establishment of restricted isolation contained in the municipal and/or state decrees/ordinances/acts of 53 selected municipalities (state capitals and those municipalities with more than 500 thousand inhabitants). Therefore, it was observed through an event study model that there was an average reduction of 8.1% in the number of elective hospitalizations and shows differences in results between the types of diseases. There was an impact of the policy mentioned above on hospitalizations for circulatory, endocrine, and neoplasm diseases and contacts with healthcare, while no effect was observed on hospitalizations for reasons of mental and behavioral disorders. The results can contribute to the formulation of new public health policies in case a situation similar to the COVID-19 pandemic occurs in the future, helping those interested in understanding the behavior of individuals in the face of the imposition of a rigid isolation policy.